INDEPENDENT WORK ON BIOLOGY AND THEIR ROLE IN EDUCATION (American Journal of Interdisciplinary Research and Development, 2022)
An important task of the school is to instill in students a conscious attitude to work, to develop the necessary practical skills, the desire for independent mastery of knowledge, interest in research, etc. School biological disciplines are of great importance in the formation of a comprehensively developed personality. Biology lessons, laboratory classes, practical work allow you to equip students with deep and solid knowledge about wildlife, as well as form their scientific and materialistic views on nature. The following article is devoted to the role of independent work in biology classes.